Associação entre complexidade das cardiopatias congênitas e o período pós operatório sob ventilação mecânica invasiva - Santos Junior, Daniel dos (2017)
Congenital heart diseases are presented as a group of conditions that account for a great number of deaths. Pointed out this complexity, several studies are focused on understanding how these can best treated by surgical procedures that could be less harmful to the patient. Invasive mechanical ventilation is one of the major supporting at the time of performing such procedures, but this could be one of the greatest complications at the time of the patient´s evolution in the ICU environment, since the moment of its withdrawal depends on many factors. Objective: The aim of this study was to evaluate whether the time required for a safety extubation following the surgical procedure would be associated to the complexity of the preoperative cardiopathy. Methodology: A total of 352 medical records of patients from a three-year period who had undergone surgery and maintained in the ICU were investigated . They were divided into two groups: neonates and non-neonates. To perform the statistical tests, six groups were created for evaluation among them, according to the degree of complexity. Rachs-1 Cardio-Surgical Risk assessment was taken into account to observe each patient´s degree of complexity. Results: Non-Neonates: Discrete male predominance in the period. When we compared the mortality according to the increase in the complexity, we could observe a statistically significant difference in four of the six evaluated groups, as well as the intubation time length , which was higher as the complexity of heart diseases increased. Regarding the estimative lines of intubation time, the best correlation was the polynomial with a 0.84-correlation coefficient, which could be feasible at the moment to evaluate intubation time. Neonates: Predominance of male sex. There was no significant difference in relation to mortality according to Rachs-1, as well as the intubation length of time. Thus, there was no statistically significant difference between the samples; this demonstrated that there was no increase in time length as the complexity increased. CONCLUSION: After assessing data and comparing them with the ones from the literature, we could conclude that the time length of patients´ intubation in the postoperative period of cardiac surgery is directly related to the complexity of the heart failure to be corrected; except in newborns from this evaluated group. The extubation time length behaved polynomially, and could be feasible to predict the patient´s extubation. Regarding the deaths, there is a relationship with a higher number according to the increase of the complexity of the heart failures, but no relationship was observed according to the case of the newborns.